Investigation of metabolite alteration in dimethylnitrosamine-induced liver fibrosis by GC–MS. (January 2013) - Ju, Hyun Kyoung; Chung, Ha Wook; Lee, Hee-Seung; Lim, Johan; Park, Jeong Hill; Lim, Sung Cil; Kim, Joon Mee; Hong, Soon-Sun; Kwon, Sung Won
Background: A metabolomic study of biomarkers associated with dimethylnitrosamine (DMN)-induced hepatic fibrosis in Sprague-Dawley rats was performed using GC–MS. The clinical chemistry of the collected blood and the histopathology of excised liver samples were examined, and urine samples were prepared by solvent extraction.Results: Through pattern analysis, the DMN-treated group was divided into two subgroups based on the aspartate aminotransferase (AST) levels compared with the control, a moderately higher group (DMN subgroup A) and a significantly higher group (DMN subgroup B). Uric acid, orotic acid, N- phenylacetylglycine and glutaric acid were biomarkers for DMN subgroup A, aminomalonic acid was a biomarker for DMN subgroup B, and arabitol level distinguished control versus DMN treatment regardless of AST level.Conclusion: This study suggests that the identification and profiling of AST level-related metabolites may be useful as a diagnostic tool and for the study of the mechanism of liver fibrosis induced by DMN.